White‐tailed deer exploit temporal refuge from multi‐predator and human risks on roads. Issue 7 (24th July 2022) - Kautz, Todd M.; Fowler, Nicholas L.; Petroelje, Tyler R.; Beyer, Dean E.; Duquette, Jared F.; Belant, Jerrold L.
Abstract: Although most prey have multiple predator species, few studies have quantified how prey respond to the temporal niches of multiple predators which pose different levels of danger. For example, intraspecific variation in diel activity allows white‐tailed deer ( Odocoileus virginianus ) to reduce fawn activity overlap with coyotes (Canis latrans ) but finding safe times of day may be more difficult for fawns in a multi‐predator context. We hypothesized that within a multi‐predator system, deer would allocate antipredation behavior optimally based on combined mortality risk from multiple sources, which would vary depending on fawn presence. We measured cause‐specific mortality of 777 adult (>1‐year‐old) and juvenile (1–4‐month‐old) deer and used 300 remote cameras to estimate the activity of deer, humans, and predators including American black bears ( Ursus americanus ), bobcats ( Lynx rufus ), coyotes, and wolves ( Canis lupus ). Predation and vehicle collisions accounted for 5.3 times greater mortality in juveniles (16% mortality from bears, coyotes, bobcats, wolves, and vehicles) compared with adults (3% mortality from coyotes, wolves, and vehicles). Deer nursery groups (i.e., ≥1 fawn present) were more diurnal than adult deer without fawns, causing fawns to have 24–38% less overlap with carnivores and 39% greater overlap with humans. Supporting our hypothesis, deer nursery groups appeared to optimize diel activity to minimize combined mortality risk. Temporal refuge for fawns was likely the result of carnivores avoiding humans, simplifying diel risk of five species into a trade‐off between diurnal humans and nocturnal carnivores. Functional redundancy among multiple predators with shared behaviors may partially explain why white‐tailed deer fawn predation rates are often similar among single‐ and multi‐predator systems. Abstract : We assessed how adult and juvenile white‐tailed deer balanced temporal overlap with humans and 4 species of carnivores, when the level of threat posed depended on deer age and the species encountered. Juvenile deer in particular exploited a "safe" temporal window in the morning and evening hours, which avoided peak human activity but capitalized on suppression of carnivores by moderate human activity. This behavior appeared optimal from radio‐collared fawn mortality, where vehicle collisions killed some fawns but were far outweighed by the combined predation of 4 carnivore species.